SOSIALISASI PENGUATAN INTEGRITAS SEBAGAI SARANA MENUMBUHKAN BUDAYA ANTI KORUPSI PADA SISWA SD IT MUHAMMADIYAH RAWALO - Puji Susanti, Rini; Wartono, Wartono; Lestari, Ega; Permatasari, Lintang Ayu (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
This Community Service Activity (PKM) is in the form of Socialization of Strengthening Integrity as a Means of Fostering Anti-Corruption Culture in SD IT Muhammadiyah Rawalo Students. This service aims to provide understanding and strengthen integrity as a means of fostering an anti-corruption culture in students to become a young generation with integrity and anti-corruption. The target target in this PKM activity is 40 students in grade V of SD IT Muhammadiyah Rawalo. This PKM was carried out by the method of lectures, interactive dialogues and the TERAJANA (KPK) game. The lecture method is used to explain the concept of corruption, 9 (nine) anti-corruption values and their application in daily life. Meanwhile, the interactive dialogue and question and answer method provided an opportunity for the participants to share their experiences about anti-corruption attitudes and behaviors. The "TERAJANA (KPK)" game method to evaluate students related to the explanation of the material that has been delivered by the service team. This PKM is also supported by an adequate PPKn Lecturer Team and supported by the enthusiasm of the participants and support from the campus (LPPM UMP) to facilitate this activity so that PKM activities are carried out properly. The obstacle faced is that students still view that corruption is an action carried out by officials only. The benefits obtained by participants from this PKM activity are that the understanding and practice of corruption can be carried out by anyone and even without realizing it can be done in daily life. Therefore, there must be self-control and practice anti-corruption values in daily life, especially in schools